EVALUATION OF HEALTH SERVICES AND MATERIAL RESOURCES FOR CERVICAL CANCER SCREENING IN OURO PRETO - MG: Health services and material resources in cervical cancer screening - Rocha e Rezende Oliveira, Renata; Aparecida de Souza Rezende, Giselle; Viana Silva , Bruna; Lage, Ana Luiza; Aparecida Martins, Bruna; Veloso, Marco Antônio; Albuquerque Geöcze, Bruna; David Souza Abreu, Ronan; Trevisan Rezende, Mariana; Martins Carneiro, Cláudia (Journal of Health Care, 2022)
The periodic Pap smear is the conventional method in Brazil for cervical cancer (CC) screening. Service strategies and material resources in the primary health centers (HC) are fundamental aspects that reflect on the quality of the screening program. Objective: To analyze four primary HC in the city of Ouro Preto, Minas Gerais and verify the local context of CC screening. Methods: A qualitative study was conducted by means of semi-structured interviews with nurses and community health agents (CHA) from the four selected UBS. Results: It was observed that only one HC had adequate physical plant and material resources to carry out the exam. In general, the CHA carried out non-systematized active search of patients to undergo the Papanicolaou test. The procedure for informing patients of altered results was similar between the UBS, however, there was no standardization for following up on altered cases. Furthermore, educational activities were scarce for the community and the work team. Conclusion: It is noticed that a quality physical structure associated with a well-trained work team promotes the establishment of successful screening programs. As it is not a reality of all local HC, it becomes necessary to implement organizational principles to systematize the strategies for active search, registration and monitoring of patients, with the CHA being fundamental in this process, due to their proximity to the population